Day-by-day symptoms following positive and negative PCR tests for SARS-CoV-2 in non-hospitalized healthcare workers: A 90-day follow-up study. (July 2021) - Nielsen, Kent J.; Vestergaard, Jesper Medom; Schlünssen, Vivi; Bonde, Jens Peter; Kaspersen, Kathrine Agergård; Biering, Karin; Carstensen, Ole; Greve, Thomas; Hansen, Karoline Kærgaard; Dalbøge, Annett; Flachs, Esben Meulengracht; Jespersen, Sanne; et al.
Highlights: 30% of mild COVID-19 patients have reduced taste and smell after 90 days. 5% of mild COVID-19 patients have dyspnoea after 30 days. Cough, sore throat, headache, muscle pain, and fever are not increased after 30 days. Women and older persons are more susceptible to COVID-19 symptoms. Abstract: Objective: Our study aimed to compare symptoms day by day for non-hospitalized individuals testing positive and negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: In total, 210 positive-test and 630 negative-test healthcare workers in the Central Denmark Region were followed for up to 90 days after testing, between April and June, 2020. Their daily reported COVID-19-related symptoms were compared graphically and by logistic regression. Results: Thirty per cent of the positive-test and close to 0% of the negative-test participants reported a reduced sense of taste and smell during all 90 days (adjusted odds ratio [aOR] 86.07, 95% CI 22.86–323). Dyspnea was reported by an initial 20% of positive-test participants, declining to 5% after 30 days, without ever reaching the level of the negative-test participants (aOR 6.88, 95% CI 2.41–19.63). Cough, headache, sore throat, muscle pain, and fever were temporarily more prevalent among the positive-test participants; after 30 days, no increases were seen. Women and older participants were more susceptible to long-lasting COVID-19 symptoms. Conclusion: The prevalence of long-lasting reduced sense of taste and smell is highly increased in mild COVID-19 patients. This pattern is also seen for dyspnea at a low level, but not for cough, sore throat, headache, muscle pain, or fever.